2007
DOI: 10.1007/s10832-007-9345-6
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature hydrothermal routes to various PZT stoichiometries

Abstract: The production of lead zirconate titanate (PZT) with a variation in Zr and Ti ratios using a hydrothermal method has been attempted. We show that when reactions are conducted at 160°C, for 4 h, the phase of PZT produced is independent of the initial Zr/Ti precursor ratio. In all cases we produce PZT with a crystal structure close to the morphotropic phase boundary, i.e. Zr/Ti≈52:48. The excess precursors either fail to react, or form amorphous and crystalline impurity phases that are detectable via powder XRD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…8, was similar to that witnessed during the hydrothermal synthesis of freestanding PZT cubes without a Pbexcess. 17 Furthermore, in contrast to the Pb-excess experiments, the islands appeared to display a layered structure. The size of the islands did not scale with reaction time, which suggests growth rates for PZT crystals on the SrTiO 3 substrates and in solution (freestanding) were comparable.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…8, was similar to that witnessed during the hydrothermal synthesis of freestanding PZT cubes without a Pbexcess. 17 Furthermore, in contrast to the Pb-excess experiments, the islands appeared to display a layered structure. The size of the islands did not scale with reaction time, which suggests growth rates for PZT crystals on the SrTiO 3 substrates and in solution (freestanding) were comparable.…”
Section: Resultsmentioning
confidence: 64%
“…The size of the islands did not scale with reaction time, which suggests growth rates for PZT crystals on the SrTiO 3 substrates and in solution (freestanding) were comparable. 17 The origin of the PZT microwires across the substrate is unclear, however certain attributes of the lines favour one explanation in particular. Firstly, their length, sometimes in excess of 1 mm, would appear to rule out crystallographic defects such as step edges, which persist over much shorter lengthscales in SrTiO 3 substrates, even after etching.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, excess of Pb 2+ enhanced the crystallization of the perovskite phase. 73) Early experimental work on hydrothermal growth of polycrystalline PZT films on Ti-substrates also showed that alkaline medium was important for the formation of the PZT solid solution. The films were grown from the alkaline (KOH) solution from Pb-nitrate Zr-oxychloride and Ti-chloride in a two-step process on Ti-metal substrates, covered with a layer of a thermally-grown oxide.…”
Section: Hydrothermal Synthesismentioning
confidence: 99%
“…In opposition to [27,31], our solution contains no titanium tetrachloride TiCl 4 because significant health hazards generally arise from the release of hydrogen chloride HCl. Rather, titanium dioxide TiO 2 , (also known as titanium(IV) oxide or titania), which is easier to handle, is preferred for preparation of a solution in combination with lead nitrate Pb(NO 3 ) 2 , zirconium oxychloride octahydrate ZrCl 2 O · 8 H 2 O, and potassium hydroxide KOH [10,16].…”
Section: Introductionmentioning
confidence: 99%